Mechanisms for Reconstructing Linguistic Interaction in Light of the Pragmatic Approach within AI-Supported Learning Contexts - Aichouche, Naima (Journal of Ecohumanism, 2026)
This article aims to analyze the mechanisms for reconstructing linguistic interaction within interdisciplinary learning contexts in light of the transformations brought about by artificial intelligence, drawing upon a pragmatic perspective that reconsiders the nature of the relationship between language and knowledge. The study is based on the problem that the transition from the multiplicity of knowledge domains to their integration cannot be achieved merely through their juxtaposition; rather, it remains dependent on the existence of linguistic interaction capable of organizing them within a coherent semantic structure, especially in a context characterized by the proliferation of discourses and the multiplicity of their sources.The research adopts an analytical pragmatic approach that seeks to deconstruct the structure of linguistic interaction in light of digital transformations and subsequently reframe it through the analysis of three central mechanisms: reformulation as a practice of reconstructing meaning, negotiation of meaning as an argumentative process for regulating interpretations, and the expansion of the pragmatic space as a reorganization of the conditions governing discourse production.The study concludes that artificial intelligence does not produce meaning in itself; instead, it redistributes the conditions of its production, thereby necessitating a shift from a technical conception of interaction toward a pragmatic one centered on its organization. Furthermore, the study demonstrates that linguistic interaction constitutes the structure within which cognitive integration is formed, rather than merely serving as a medium for its transmission. Consequently, reconstructing such interaction becomes a fundamental approach to reframing learning within contemporary interdisciplinary contexts.